Scalp high-frequency oscillation rates are higher in younger children. Issue 2 (23rd March 2021) - Cserpan, Dorottya; Boran, Ece; Lo Biundo, Santo Pietro; Rosch, Richard; Sarnthein, Johannes; Ramantani, Georgia
Abstract: High-frequency oscillations in scalp EEG are promising non-invasive biomarkers of epileptogenicity. However, it is unclear how high-frequency oscillations are impacted by age in the paediatric population. We prospectively recorded whole-night scalp EEG in 30 children and adolescents with focal or generalized epilepsy. We used an automated and clinically validated high-frequency oscillation detector to determine ripple rates (80–250 Hz) in bipolar channels. Children < 7 years had higher high-frequency oscillation rates ( P  =   0.021) when compared with older children. The median test−retest reliability of high-frequency oscillation rates reached 100% (iqr 50) for a data interval duration of 10 min. Scalp high-frequency oscillation frequency decreased with age ( r = −0.558, P  =   0.002), whereas scalp high-frequency oscillation duration and amplitude were unaffected. The signal-to-noise ratio improved with age ( r  = 0.37, P  =   0.048), and the background ripple band activity decreased with age ( r = −0.463, P  =   0.011). We characterize the relationship of scalp high-frequency oscillation features and age in paediatric patients. EEG intervals of ≥ 10 min duration are required for reliable measurements of high-frequency oscillation rates. This study is a further step towards establishing scalp high-frequency oscillations as a valid epileptogenicity biomarker in this vulnerable age group. Abstract : Cserpan et al. report the impact of age on high-frequency oscillations recorded in the scalp EEG of children with epilepsy. Children <7 years had higher rates of high-frequency oscillations when compared with older children. EEG intervals of ≥10 min were required for the reliable estimation of these rates. Graphical Abstract: